Challenging social norms: discourse analysis of a research project aiming to use financial incentives to change breastfeeding behaviours. (November 2017) - Relton, Clare; Umney, Darren; Strong, Mark; Thomas, Kate; Renfrew, Mary J
Abstract: Background: The UK has one of the lowest breastfeeding rates in the world. The NOurishing Start for Health (NOSH) cluster-randomised trial was a trial of a financial incentive scheme that aimed to increase breastfeeding in UK areas where breastfeeding was not the norm (South Yorkshire, Derbyshire, and Nottinghamshire). The announcement of the initial field test of the Vouchers for Breastfeeding scheme generated a substantial amount of (mainly negative) media and social media coverage. Given the media interest and scrutiny in public health research and action (especially where financial incentives are concerned), we aimed to understand negative responses, and the underlying values they represent, to inform future public health research into financial incentives. Methods: A researcher (DU) external to the project and the research area led a discourse analysis of the research project archive, drawing upon more than 500 documents that included team briefs, scholarly articles, publicity material, media reports, and online responses. The purpose of the analysis was to identify where conflicting values were apparent, particularly those at critical transition points in the project, which facilitated further content and visual analysis of relevant documents. Findings: The analysis exposed fundamental, opposing, and apparently intractable views on the use of financial incentives to increase breastfeeding in the UK. These conflicting positions were apparent from the early stages of the research project and recurred at critical points during the development and delivery of the scheme. In contrast to local stakeholder views, media and social media commentators tended to marginalise the research question and focus instead on discussing why offering incentives for breastfeeding should not be national policy. The analysis also revealed how the project researchers used extensive stakeholder consultation, deployed sensitive language in all public engagements, and adapted well-established visual representations of financial incentives, to navigate through the inherent controversy. Interpretation: Projects that challenge societal behavioural norms should anticipate strong and sometimes hostile reactions when planning and progressing their research. Also, researchers should not assume that media and social media reactions represent the considered views of stakeholders directly affected by the research, which in this case were mothers (and their health-care providers) in the areas where the scheme was being trialled. Funding: Medical Research Council (MR/J000434/1) via the National Prevention Research Initiative Phase 4 awards.